Environmental Consequences of Water Withdrawals and Drainage of Wetlands - Alan L. Wright (EDIS)
SL-302, a 3-page fact sheet by Alan L. Wright, educates the general public about how hydrologic conditions, such as drought and water withdrawal, influence the functioning and benefits of wetland ecosystems. Includes additional sources of information. Published by the UF Department of Soil and Water Science, July 2009.